Caregivers dying before care recipients with dementia. Issue 1 (24th November 2018) - Gaugler, Joseph E.; Jutkowitz, Eric; Peterson, Colleen M.; Zmora, Rachel
Abstract: Introduction: Although a handful of studies have examined mortality among caregivers of persons with Alzheimer's disease or a related dementia (ADRD), the proportion of caregivers who die before their cognitively impaired care recipients remains unknown. Methods: We conducted descriptive and survival analyses on up to 17 years of data from the nationally representative Health and Retirement Study to evaluate the proportion of spouse caregivers who died before their care recipients. Results: Eighteen percent of spouse ADRD caregivers died before their care recipients, and spouse caregivers had a significantly lower risk of mortality than their husbands or wives with ADRD. Discussion: Although a large majority of spouse ADRD caregivers will likely not die before their cognitively impaired husband or wife, those persons with ADRD who survive longer than their caregivers are worthy of future inquiry given their potential risk for negative health outcomes.